2013
DOI: 10.1007/s00267-013-0212-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Published Information in Reviewing Conservation Objectives for Natura 2000 Protected Areas in the European Union

Abstract: Protected areas are designated to protect species and other features known to be present at the time of designation, but over time the information about the presence of protected species may change and this should call for a continued review of conservation objectives. Published scientific literature is one of the possible information sources that would trigger a review of conservation objectives. We studied how published data on new discoveries of protected animal species were taken into account by the nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…This finding can be interpreted as a direct result of the ongoing efforts to expand the N2K network [1], [9], but also a reflection of the low levels of penetration of social and political sciences in the field of conservation science [46], [47], [48]. Social sciences are integral to the discipline of conservation biology [19], yet the current conceptual, methodological, and epistemic gaps between the disciplines addressing ecology and society continue to hinder social and policy research in and for conservation [36].…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…This finding can be interpreted as a direct result of the ongoing efforts to expand the N2K network [1], [9], but also a reflection of the low levels of penetration of social and political sciences in the field of conservation science [46], [47], [48]. Social sciences are integral to the discipline of conservation biology [19], yet the current conceptual, methodological, and epistemic gaps between the disciplines addressing ecology and society continue to hinder social and policy research in and for conservation [36].…”
Section: Discussionmentioning
confidence: 85%
“…This finding could be partially explained by factors not directly related to the topic of the papers; for example, taxon-specific research is highly fragmented among journals [9], which may have different keyword requirements (e.g., number of keywords, avoidance of words used in title). The distribution of keywords by degree and betweenness highlighted the most frequently addressed topics within each of the study types but also revealed critical concepts that link articles within fields of study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations